Boiler Performance with Variations in Fuel Mix Composition Feeding - Winarto, Adi Putra; Sari, Dessy Agustina (Universitas Khairun, 2024)
PKS Kertajaya is a subsidiary of PTPN VIII, which focuses on the palm oil industry. a number of main processing and supporting equipment for this factory. One of the key aspects of the production process is the use of the boiler. This equipment produces steam, which is needed by various palm oil production processes and even factory utility areas. Therefore, the research study focused on the quantity of fuel used in producing the steam. The palm oil industry utilizes the solid waste from fresh fruit bunches, namely fibers and shells. The variable variation is in the percentage of the two fuels. From the estimation results using the direct method, it was found that the feeding conditions of 50:50, 60:40, and 70:30% were able to provide an increase in boiler efficiency values along with decreasing operational fuel costs. However, if you compare it with the quantity of fuel that has been applied by the industry, the percentage of 50:50% is the optimum condition, both in terms of boiler efficiency and economic value, which is one level higher than the current condition. This consideration is viewed from the estimation side as well as the amount of carbon content owned. Apart from that, the palm oil industry continues to maintain performance during routine maintenance of boiler equipment. Ingredients other than carbon are able to make short- to long-term contributions to producing steam. PKS Kertajaya merupakan anak perusahaan PTPN VIII yang berfokus di bidang industri kelapa sawit. Dari sejumlah peralatan utama proses maupun pendukung pabrik ini. Ssalah satu aspek kunci proses produksinya berada pada penggunaan boiler. Peralatan ini menghasilkan uap air yang dibutuhkan ragam proses produksi minyak kelapa sawit bahkan area utilitas pabrik. Oleh karena itu, kajian penelitian difokuskan ke kuantitas bahan bakar yang digunakan dalam memproduksi steam tersebut. Pihak industri kelapa sawit memanfaatkan peran limbah padat dari tandan buah segar, yaitu serabut dan cangkang. Variasi variabel berada pada persentase kedua bahan bakar tersebut. Dari hasil estimasi melalui penggunaan metode langsung didapatkan bahwa kondisi pengumpanan 50:50, 60:40, dan 70:30% mampu memberikan peningkatan nilai efisiensi boiler dengan seiring menurunnya biaya operasional bahan bakar. Akan tetapi, jika membandingkan dengan kuantitas bahan bakar yang telah diterapkan pihak industri maka persentase 50:50% adalah kondisi optimum baik sisi efisiensi boiler dan nilai ekonomi yang lebih tinggi satu tingkat dari kondisi saat ini. Pertimbangan ini ditinjau dari sisi estimasi dan juga jumlah kandungan karbon yang dimiliki. Selain itu, pihak industri kelapa sawit tetap menjaga performa selama terutama pelaksanaan perawatan rutin peralatan boiler. Kandungan selain karbon mampu memberikan kontribusi baik jangka pendek hingga panjang dalam memproduksi uap air.